A redução segmental em sequências #(i)sC no português brasileiro - Matheus Freitas Gomes (2019)
This dissertation aims at investigating the variable segmental reduction in initial #(i)sC sequences in the Belo Horizonte variety of Brazilian Portuguese, in words such as escola [iskl] ~ [skl] ou skate [iske] ~ [ske]. This investigation focuses on how segmental reduction is implemented and its relationship with different orthographic patterns. We aim to demonstrate that the #(i)sC syllabic pattern is gradually reorganised with lexical impact. Moreover, we assess how different orthographic patterns are related to different levels of segmental reduction in #(i)sC. The analysed words presented two different orthographic patterns: #ESC, which is predicted by Portuguese writing system, or #SC, which is related to loanwords. As a theoretical approach, we adopted Exemplar Theory (JOHNSON, 1997; PIERREHUMBERT, 2001) and models that integrate orthographic knowledge and phonological representation (LEVITT, 1979; TAFT, 1982; MATTINGLY, 1992; SILVEIRA, 2017; HAMANN; COLOMBO, 2017). The methodology is based on Laboratory Phonology perspective (PIERREHUMBERT; BECKMAN; LADD, 2011 [2000]). Data were composed by recordings of 30 words by 24 speakers from Belo Horizonte. 1.440 tokens for #(i)sC were examined. Three analyses were carried out. In the first analysis the occurrence of the vowel in #(i)sC sequences was investigated, considering the following factors: orthographic pattern, lexical item, sex, and speaker. It was found out that the #ESC pattern favours the production of the vowel when compared to #SC pattern. Moreover, each lexical item had particular indices of vowel occurrence, indicating that there is lexical gradualness in the phenomenon implementation. In the second analysis vowel duration and sibilant duration in #(i)sC sequences were investigated. For vowel duration, the following factors were considered: orthographic pattern, and lexical item. For sibilant duration, the following factors were considered: vowel occurrence, vowel duration, and orthographic pattern. In #SC words the initial vowel is shorter than it is in #ESC words. In segmental reduction context, the sibilant is lengthened. In the third analysis vowel quality in #(i)sC sequences was investigated, considering the effects of the orthographic pattern. Results show that the [i] vowel in #SC words has significant smaller vowel space than the [i] vowel in #ESC words, presenting a more centralised quality. This dissertation results offer evidence to regard sound variation and sound change phenomena as lexically and phonetically implemented. and to include orthography as a factor in a phonological analysis. The results also confirm that orthography is a factor that may be included in phonological investigations.